2019
DOI: 10.3390/vaccines7020042
|View full text |Cite
|
Sign up to set email alerts
|

Designed DNA-Encoded IL-36 Gamma Acts as a Potent Molecular Adjuvant Enhancing Zika Synthetic DNA Vaccine-Induced Immunity and Protection in a Lethal Challenge Model

Abstract: Identification of novel molecular adjuvants which can boost and enhance vaccine-mediated immunity and provide dose-sparing potential against complex infectious diseases and for immunotherapy in cancer is likely to play a critical role in the next generation of vaccines. Given the number of challenging targets for which no or only partial vaccine options exist, adjuvants that can address some of these concerns are in high demand. Here, we report that a designed truncated Interleukin-36 gamma (IL-36 gamma) encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Louis et al reported that a truncated IL-36g-encoded plasmid can act as a potent adjuvant for a DNA-encoded Zika virus (ZIKV) vaccine. Immunization with truncated IL-36g promoted antiviral T cell responses and protected mice from ZIKV challenge (68). Moreover, co-delivery of truncated IL-36g can also enhance antiviral immunity against HIV and influenza DNA vaccines (68).…”
Section: Other Organsmentioning
confidence: 99%
“…Louis et al reported that a truncated IL-36g-encoded plasmid can act as a potent adjuvant for a DNA-encoded Zika virus (ZIKV) vaccine. Immunization with truncated IL-36g promoted antiviral T cell responses and protected mice from ZIKV challenge (68). Moreover, co-delivery of truncated IL-36g can also enhance antiviral immunity against HIV and influenza DNA vaccines (68).…”
Section: Other Organsmentioning
confidence: 99%
“…Vaccination with highly optimized DNA cancer vaccines and delivered by the CELLECTRA R electroporation (EP) device for cancer has been highly effective in the preclinical space (7)(8)(9)(10)(11) and results from a phase 2b clinical trial testing VGX-3100 for patients with cervical intraepithelial neoplasia showed this therapy to be safe, efficacious, and immunogenic (12). It has been well-documented that the specific targeting of immune cells by molecular adjuvants increases the immune response to viral associated antigens (13)(14)(15)(16), thus the potential exists to further increase the magnitude of the vaccine-elicited responses against tumor-associated antigens (TAAs) enabling tumor control.…”
Section: Introductionmentioning
confidence: 99%
“…Hit by the COVID-19 epidemics, the world has come to realize the importance of efficient vaccines against viral infections. It is comforting that the contributing authors were working hard in this field before the epidemic broke out: all publications of this issue focus on the development of vaccines against viral infections, such as HIV by Kilpelainen et al [1], Louis et al [2], and Akulova et al [3]; human hepatitis C virus by Masalova et al [4]; Ebola virus by Bazhan et al [5]; Zika virus [2]; influenza by Hinkula et al [6] and Louis et al [2]; and Epstein-Barr virus by Wojtak et al [7].…”
mentioning
confidence: 99%
“…The majority of studies presented in this issue used different forms of plasmid DNA: genes optimized for expression and/or consensus immunogens [2,3,7], polyepitope constructs [5], or plasmids with viral enhancers increasing protein expression and thus allowing one to reduce the DNA dose (Chapman & Rybicki [8]). A still more efficient way to ensure high-level expression of the immunogen is to use RNA/DNA layered alphavirus vectors, which provide a superior expression of immunogens in comparison with conventional plasmid DNA technology (Lundstrom [9]).…”
mentioning
confidence: 99%
See 1 more Smart Citation